Gender-Specific Impacts of Road Improvement : What Can Be Done to Ensure that Better Roads Expand Economic Opportunities for All? - World Bank (World Bank, Washington, DC, 2020)
How and why do the benefits of better transport differ between genders? A non-experimental impact evaluation of a large-scale rural roads project in Vietnam combined with qualitative data collection suggests some possibilities. While roads improve trading opportunities for all households, only households headed by men are able to increase agricultural output and income. Lower levels of household labor and capital in female-headed households seems to constrain their ability to make similar changes. The implications for policy are that coordinating transport investments with complementary development programs can address constraints faced by female-headed and poor households and improve the benefits of better transport for them.